2012
DOI: 10.4067/s0718-95162012005000009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc and manganese as foliar spray on pomegranate yield, fruit quality and leaf minerals

Abstract: Effects of foliar sprays of zinc and manganese sulfates on the fruit yield and quality as well as leaf nutrients concentration of pomegranate were studied during 2010 growing season in an orchard with a soil pH of 7.5 and EC of 5.2 (dS m -1 ). Zinc and manganese sulfates were applied two times at the rate of 0, 0.3 and 0.6 percent under a factorial design on the base of completely randomized blocks. Mn sprays had positive significant effects on the fruit yield, the aril/peel ratio, TSS, weight of 100 arils, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
52
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 14 publications
17
52
2
3
Order By: Relevance
“…Total soluble solid contents of the cultivars vary from 16.00 to 21.45. These findings are in accordance with the results of other works [15,19,20]. Among the studied cultivars, Wonderful has the TSS content of 21.45 followed by Acco (17.29) and Herskovitz (16.00).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Total soluble solid contents of the cultivars vary from 16.00 to 21.45. These findings are in accordance with the results of other works [15,19,20]. Among the studied cultivars, Wonderful has the TSS content of 21.45 followed by Acco (17.29) and Herskovitz (16.00).…”
Section: Discussionsupporting
confidence: 82%
“…The Acco and Herskovitz are early cultivars with smaller dimensions and less ripening period than Wonderful. The yield of three cultivars of 4 and 5 years old is found to be superior over the fruit yield of Malas e Torsh e Saveh (Iran cultivars; 8.10 kg/tree) [19]. It is observed that some orchards have recorded significant difference in fruit yield as reported here: 31.6 kg/tree for Wonderful, 31.4 kg/tree for Acco and 39.8 kg/tree for Herskovitz.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, maximum length (6.18 cm), diameter (5.46 cm) and volume (120.28 cc) of fruit was obtained with the foliar application of zinc sulphate (0.4%). Hasani et al, (2012) conducted an experiment on effects of foliar sprays of zinc on the fruit yield and quality in pomegranate. Zinc was applied twice at the rate of 0, 0.3 and 0.6 percent.…”
Section: Essentiality and Deficiency Symptoms Of Zincmentioning
confidence: 99%